Timing of onset of gastrointestinal bleeding in the ICU: Protocol for a preplanned observational study. Issue 8 (14th May 2018) - Granholm, A.; Lange, T.; Anthon, C. T.; Marker, S.; Krag, M.; Meyhoff, T. S.; Wise, M. P.; Borthwick, M.; Bendel, S.; Keus, F.; Guttormsen, A. B.; Schefold, J. C.; et al.
Abstract : Background: Critically ill patients are at risk of gastrointestinal bleeding, but clinically important gastrointestinal bleeding is rare. The majority of intensive care unit (ICU) patients receive stress ulcer prophylaxis (SUP), despite uncertainty concerning the balance between benefit and harm. For approximately half of ICU patients with gastrointestinal bleeding, onset is early, ie within the first two days of the ICU stay. The aetiology of gastrointestinal bleeding and consequently the balance between benefit and harm of SUP may differ between patients with early vs late gastrointestinal bleeding. Methods: This is a protocol and statistical analysis plan for a preplanned exploratory substudy of the Stress Ulcer Prophylaxis in the Intensive Care Unit (SUP‐ICU) randomized clinical trial, comparing intravenous pantoprazole (40 mg once daily) with placebo in 3350 acutely ill adult ICU patients. We will describe baseline characteristics and assess the time to onset of the first clinically important episode of GI bleeding accounting for survival status and allocation to SUP or placebo. In addition, we will describe differences in therapeutic and diagnostic procedures used in patients with clinically important gastrointestinal bleeding according to early vs late bleeding and 90‐day vital status. Conclusions: The study outlined in this protocol will provide detailed information on patient characteristics and the timing of onset of gastrointestinal bleeding in the patients enrolled in the SUP‐ICU trial. This may provide additional knowledge and incentives for future studies on which patients benefit from SUP.